Transcriptional mechanism of IRF8 and PU.1 governs microglial activation in neurodegenerative condition - Nan Zhou; Kaili Liu; Yue Sun; Ying Cao; Jing Yang (Protein & Cell, 2018)
ABSTRACT Microglial activation occurs in divergent neuropathological conditions. Such microglial event has the key involvement in the progression of CNS diseases. However, the transcriptional mechanism governing microglial activation remains poorly understood. Here, we investigate the microglial response to traumatic injury-induced neurodegeneration by the 3D fluorescence imaging technique. We show that transcription factors IRF8 and PU.1 are both indispensible for microglial activation, as their specific post-developmental deletion in microglia abolishes the process. Mechanistically, we reveal that IRF8 and PU.1 directly target the gene transcription of each other in a positive feedback to sustain their highly enhanced expression during microglial activation. Moreover, IRF8 and PU.1 dictate the microglial response by cooperatively acting through the composite IRF-ETS motifs that are specifically enriched on microglial activation-related genes. This action of cooperative transcription can be further verified biochemically by the synergetic binding of IRF8 and PU.1 proteins to the composite-motif DNA. Our study has therefore elucidated the central transcriptional mechanism of microglial activation in response to neurodegenerative condition.